2016
DOI: 10.1186/s12913-016-1821-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and health outcomes among Asian Indians in the United States

Abstract: BackgroundPerceived interpersonal discrimination while seeking healthcare services is associated with poor physical and mental health. Yet, there is a paucity of research among Asian Americans or its subgroups.This study examined the correlates of reported interpersonal discrimination when seeking health care among a large sample of Asian Indians, the 3rd largest Asian American subgroup in the US, and identify predictors of adverse self-rated physical health, a well-accepted measure of overall health status.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 60 publications
0
22
1
Order By: Relevance
“…Adjusting for other tested factors did not affect this association. The results differ from previous studies in which the used factors have been associated with unmet need for medical care 3,5,6,12,15,16,[18][19][20][21][22]24,26,27 . The strong association could be due to a bi-directional relationship between the discriminatory treatment and unmet need for care.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Adjusting for other tested factors did not affect this association. The results differ from previous studies in which the used factors have been associated with unmet need for medical care 3,5,6,12,15,16,[18][19][20][21][22]24,26,27 . The strong association could be due to a bi-directional relationship between the discriminatory treatment and unmet need for care.…”
Section: Discussioncontrasting
confidence: 99%
“…Perceived unjust treatment has also been linked to poorer self-rated health 8,20 which is a widely accepted predictor of both morbidity and mortality 23 . Those that report poor self-rated health or have existing chronic illnesses often also express greater need for medical care than others 3,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination, too, has been reported elsewhere: two studies on minority populations in the United States (US) and a study on immigrants in Spain also highlights that these groups experienced discrimination within healthcare settings [ 26 , 29 , 30 ]. Another in-depth study conducted in Thailand found that Sub-Saharan African migrants living in Bangkok experienced a high level of dissatisfaction with the services provided by health professionals [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…43,44 All participants reported how well they spoke English, with options including very well, well, and not well. 45 …”
Section: Smoking and Acculturation Among Latinos -Pulvers Et Almentioning
confidence: 99%